Overview of non-invasive sampling methods used in intensive swine farming - Glisic, Dimitrije; Veljović, Ljubiša; Milovanović, Bojan; Ninković, Milan; Maletić, Jelena; Kureljušić, Branislav; Milićević, Vesna (Veterinarski Glasnik, 2023)
Monitoring the health of swine herds is essential to ensure good manufacturing practices. Traditionally, active and passive surveillance on farms involved invasive sampling methods, where specific animals were selected, restrained, and sampled. However, with the increasing intensity of swine production, alternative methods for effective herd surveillance became necessary. Non-invasive sampling provides a convenient and cost-effective approach to monitor the entire herd without compromising animal welfare, while still obtaining suitable samples for testing. Oral fluids have been widely used in both human and livestock health surveillance for various viral pathogens, including significant diseases. Nasal wipes (NW) utilize different cloth materials soaked in phosphate-buffered saline (PBS) or tissue culture medium with antibiotics and antimycotics to sample for swine influenza virus (SIV). Udder skin wipes (USW) offer an alternative method to assess the health status of piglets in a litter. During routine procedures such as tail docking and castration, a mixture of blood and serum can be collected, known as process fluids (PF), which has proven successful in monitoring herds for the presence of porcine reproductive and respiratory syndrome virus (PRRSV). Furthermore, air sampling has emerged as a novel technique to detect pathogens in various farming systems and animal species. This method offers the advantage of obtaining diagnostic samples without direct animal contact. By employing these non-invasive sampling methods, swine producers can implement effective surveillance strategies while maintaining animal welfare standards and obtaining reliable diagnostic information.